Analysis of the deformation behavior of Ti-6Al-4V at elevated temperatures - Merklein, Marion; Hagenah, Hinnerk; Kaupper, Markus; Schaub, Adam (Key Engineering Materials, 2013)
Titanium alloys, such as Ti-6Al-4V, offer favorable characteristics as significant strength, biocompatibility and metallurgical stability at elevated temperatures. These advantages afford the application of parts out of Ti-6Al-4V in a wide field within aerospace, astronautic and medical technologies. Most applied shaping operations for parts out of titanium alloys are forging, casting, forming and machining. In order to develop and improve forming operations numerical simulations are applied during preprocessing. For that purpose mechanical properties of the material such as yield stress and Lankford parameter have to be determined. Due to the two-phase (α + β) microstructure of Ti-6Al-4V, forming operations have to be carried out at elevated temperatures to reduce the required forming force and extend forming limits. Taking the temperature and stress state dependency of the material into consideration, uniaxial tensile and compression tests are accomplished at elevated temperatures, ranging from 400 to 600 °C. Furthermore, the experimenttally determined yield stress and Lankford parameter are approximated with the yield loci model proposed by Barlat 2000. The model predicts the flow response of the material, thus provides input data for the finite element analysis of forming processes at different temperature levels. Copyright © 2013 Trans Tech Publications Ltd.
LFT Import::2019-07-29 (1876)
Keywords: Compression test; Temperature effects; Tensile test; Ti-6AL-4V alloy; Yield loci